Multi-Platform Sequencing Approach Reveals a Novel Transcriptome Profile in Pseudorabies Virus - Moldován, Norbert; Tombácz, Dóra; Szűcs, Attila; Csabai, Zsolt; Snyder, Michael; Boldogkői, Zsolt (Frontiers in Microbiology, 2018)
Third-generation sequencing is an emerging technology that is capable of solving several problems that earlier approaches were not able to, including the identification of transcripts isoforms and overlapping transcripts. In this study, we used long-read sequencing for the analysis of pseudorabies virus (PRV) transcriptome, including Oxford Nanopore Technologies MinION, PacBio RS-II, and Illumina HiScanSQ platforms. We also used data from our previous short-read and long-read sequencing studies for the comparison of the results and in order to confirm the obtained data. Our investigations identified 19 formerly unknown putative protein-coding genes, all of which are 5’ truncated forms of earlier annotated longer PRV genes. Additionally, we detected 19 non-coding RNAs, including 5’ and 3’ truncated transcripts without in-frame ORFs, antisense RNAs, as well as RNA molecules encoded by those parts of the viral genome where no transcription had been detected before. This study has also led to the identification of three complex transcripts and fifty distinct length isoforms, including transcription start and end variants. We also detected 121 novel transcript overlaps, and two transcripts that overlap the replication origins of PRV. Furthermore, in silico analysis revealed 145 upstream ORFs, many of which are located on the longer 5’ isoforms of the transcripts.